2014
DOI: 10.1371/journal.pone.0088161
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Differentially Modulates Firing Rate of Solitary Complex (SC) Neurons from Control and Chronic Hypoxia-Adapted Adult Rats

Abstract: NK1 receptors, which bind substance P, are present in the majority of brainstem regions that contain CO2/H+-sensitive neurons that play a role in central chemosensitivity. However, the effect of substance P on the chemosensitive response of neurons from these regions has not been studied. Hypoxia increases substance P release from peripheral afferents that terminate in the caudal nucleus tractus solitarius (NTS). Here we studied the effect of substance P on the chemosensitive responses of solitary complex (SC:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…SP and the NK1R have been shown to play an integral role in the modulation of homeostatic function in the medulla, including regulation of respiratory rhythm generation [ 14 16 ], integration of cardiovascular control [ 17 ], modulation of the baroreceptor reflex [ 18 ] and mediation of the chemoreceptor reflex in response to hypoxia [ 19 , 20 , 28 ]. In this study, we observed abnormalities related to development and sex in NK1R binding within multiple nuclei of the medullary homeostatic network in SIDS cases incuding absolute reductions in binding in the NTS and and all sub-divisions of IO nuclei (PIO, MAO, DAO).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SP and the NK1R have been shown to play an integral role in the modulation of homeostatic function in the medulla, including regulation of respiratory rhythm generation [ 14 16 ], integration of cardiovascular control [ 17 ], modulation of the baroreceptor reflex [ 18 ] and mediation of the chemoreceptor reflex in response to hypoxia [ 19 , 20 , 28 ]. In this study, we observed abnormalities related to development and sex in NK1R binding within multiple nuclei of the medullary homeostatic network in SIDS cases incuding absolute reductions in binding in the NTS and and all sub-divisions of IO nuclei (PIO, MAO, DAO).…”
Section: Discussionmentioning
confidence: 99%
“…The NTS houses the primary relay station for brainstem transmission of important respiratory and cardiovascular reflexes and is enriched with a high density of SP containing axon terminals [ 29 , 30 ]. Evidence from animal studies indicates a functional role for SP in the NTS as a central integrator of cardiovascular control [ 17 ], modulator of baroreceptor reflex sensitivity [ 18 ] and a primary excitatory mediator of the chemoreceptor reflex in response to hypoxia [ 19 , 20 ]. In rodent models, activation of NK1R by SP in the NTS stimulates respiration, while loss of NK1R reduces the respiratory response, severely impairing the chemoreceptor reflex and selective lesion of NK1R expressing neurons in the NTS blunts cardiovascular reflexes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The altered expression and/or function of the neuropeptide Substance P and its receptor, the Neurokinin‐1 receptor (NK1R), have also been suggested to play a role in the pathogenesis of SIDS 8–11 . They play key roles in mechanisms thought to contribute to SIDS including the modulation of homeostatic function in the medulla, involving regulation of respiratory rhythm generation, 12,13 integration of cardiovascular control, 14 modulation of the baroreceptor reflex 15 and mediation of the chemoreceptor reflex in response to hypoxia 16,17 . Furthermore, in rodent models the activation of NK1R by Substance P in the nucleus tractus solitarii (NTS) stimulates respiration, while loss of NK1R reduces the respiratory response, severely impairing the chemoreceptor reflex.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 They play key roles in mechanisms thought to contribute to SIDS including the modulation of homeostatic function in the medulla, involving regulation of respiratory rhythm generation, 12 , 13 integration of cardiovascular control, 14 modulation of the baroreceptor reflex 15 and mediation of the chemoreceptor reflex in response to hypoxia. 16 , 17 Furthermore, in rodent models the activation of NK1R by Substance P in the nucleus tractus solitarii (NTS) stimulates respiration, while loss of NK1R reduces the respiratory response, severely impairing the chemoreceptor reflex. The selective disruption of NK1R expressing neurons in the NTS reduces cardiovascular reflexes.…”
Section: Introductionmentioning
confidence: 99%